Dogs Can Be Successfully Trained to Alert to Hypoglycemia Samples from Patients with Type 1 Diabetes - Hardin, Dana S. (Diabetes Ther, 2015)
INTRODUCTION: Hypoglycemia (Hypo) is the most common side effect of insulin therapy in people with type 1 diabetes (T1D). Over time, patients with T1D become unaware of signs and symptoms of Hypo. Hypo unawareness leads to morbidity and mortality. Diabetes alert dogs (DADs) represent a unique way to help patients with Hypo unawareness. Our group has previously presented data in abstract form which demonstrates the sensitivity and specificity of DADS. The purpose of our current study is to expand evaluation of DAD sensitivity and specificity using a method that reduces the possibility of trainer bias. METHODS: We evaluated 6 dogs aging 1–10 years old who had received an average of 6 months of training for Hypo alert using positive training methods. Perspiration samples were collected from patients during Hypo (BG 46–65 mg/dL) and normoglycemia (BG 85–136 mg/dl) and were used in training. These samples were placed in glass vials which were then placed into 7 steel cans (1 Hypo, 2 normal, 4 blank) randomly placed by roll of a dice. The dogs alerted by either sitting in front of, or pushing, the can containing the Hypo sample. Dogs were rewarded for appropriate recognition of the Hypo samples using a food treat via a remote control dispenser. The results were videotaped and statistically evaluated for sensitivity (proportion of lows correctly alerted, “true positive rate”) and specificity (proportion of blanks + normal samples not alerted, “true negative rate”) calculated after pooling data across all trials for all dogs. RESULTS: All DADs displayed statistically significant (p value <0.05) greater sensitivity (min 50.0%–max 87.5%) to detect the Hypo sample than the expected random correct alert of 14%. Specificity ranged from a min of 89.6% to a max of 97.9% (expected rate is not defined in this scenario). CONCLUSIONS: Our results suggest that properly trained DADs can successfully recognize and alert to Hypo in an in vitro setting using smell alone. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13300-015-0135-x) contains supplementary material, which is available to authorized users.